A kinetic study of mercury(II) transport through a membrane assisted by new transport reagent - Karakus, Mehmet; Alpoguz, Hamza Korkmaz; Kaya, Ahmet; Acar, Nurcan; Gorgulu, Ahmet Orhan; Arslan, Mustafa (Biomed Central Ltd, 2011)
Background: A new organodithiophosphorus derivative, namely O-(1,3-Bispiperidino-2-propyl)-4-methoxy phenyldithiophosphonate, was synthesized and then the kinetic behavior of the transport process as a function of concentration, temperature, stirring rate and solvents was investigated. Results: The compound 1 was characterized by elemental analysis, IR, H-1 and P-31 NMR spectroscopies. The transport of mercury(II) ion by a zwitterionic dithiophosphonate 1 in the liquid membrane was studied and the kinetic behavior of the transport process as a function of concentration, temperature, stirring rate and solvents was investigated. The compound 1 is expected to serve as a model liquid membrane transport with mercury(II) ions. Conclusion: A kinetic study of mercury(II) transport through a membrane assisted by O-(1,3-Bispiperidino-2-propyl)4-methoxy phenyldithiophosphonate was performed. It can be concluded that the compound 1 can be provided a general and straightforward route to remove toxic metals ions such as mercury(II) ion from water or other solution.
Keywords: Bulk Liquid-Membrane; Electrical-Conductivity; Coupled Transport; Cu(Ii) Ions; Ligands; Carrier; Coordination; Complexes; Extraction; Chemistry